The Empirical Research on Violence in Mexican Schools from the Voices of Students: Critical Points - Zurita Rivera, Ursula (2019)
The growing visibility of violence in schools has caused multiple demands to know their condition in our societies. Given this, the conceptual, analytical and methodological challenges faced between those engaged in their empirical research are evident. However, many of those who face these challenges do not analyze the parallel processes that are configured as the research progresses. This is the case of changes about the role of students in this collective effort. The objective of this document is to analyze the advances and dilemmas of the empirical research on violence in Mexico, focusing on the implications derived from the legitimization of the voices of children and adolescents. This analysis based on the specialized literature on school violence and the voices of students, warns that although studies that conceive these populations as individuals capable of providing data on this phenomenon through the application of numerous research techniques have been generalized, the idea of assuming them as sources of information and as passive and subordinated recipients of decisions and actions taken by adults. This analysis is aimed at experts, authorities and social leaders who, when considering the students as interlocutors in the empirical research on school violence, are committed to the recognition of the right to participation of children and adolescents, and the promotion of its effective exercise in schools.